Questions of formation of musical culture of the person during reading the notes from a sheet (Pedagogy of Higher and Secondary Education, 2006)
The article considers the general provisions and components of receptions of reading of the notes from a sheet, methodical receptions offormation of skill and training of high-speed reactions an musical marks and musical culture of the person.
Keywords: reading of the notes from a sheet; musical activity; any movements; skill of orientation; stage; methods; representations; speed of reactions; musical mark